2017
DOI: 10.1038/srep40561
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the biochemical and chemical properties of badland soils by thorny bamboo

Abstract: Badland soils—which have high silt and clay contents, bulk density, and soil electric conductivity— cover a large area of Southern Taiwan. This study evaluated the amelioration of these poor soils by thorny bamboo, one of the few plant species that grows in badland soils. Soil physiochemical and biological parameters were measured from three thorny bamboo plantations and nearby bare lands. Results show that bamboo increased microbial C and N, soil acid-hydrolysable C, recalcitrant C, and soluble organic C of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
0
20
2
Order By: Relevance
“… Note . pH, soil moisture, EC, organic C and total N contents were from Shiau et al (). Results are means ( SD ) of three replicates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Note . pH, soil moisture, EC, organic C and total N contents were from Shiau et al (). Results are means ( SD ) of three replicates.…”
Section: Resultsmentioning
confidence: 99%
“…They are also low in organic matter. The study of Shiau et al () indicated that the thorny bamboo plantation in the same badland regions helped to improve soil physicochemical properties (e.g., increased organic C and water holding capacity and decreased in soil bulk density). Bamboo plantation also resulted in increasing microbial C and N and soluble organic C. The microbial biomass C to total organic C ratio was higher in bamboo plantations than bare land soils, suggesting that microbes utilize soil organic matter more efficiently in bamboo soils (Shiau et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo is important in the recovery of soil physiochemical properties (Christanty, Kimmins & Mailly, 1997; Embaye et al, 2005; Shiau et al, 2017), soil redevelopment (Singh & Singh, 1999) and soil nutrients, especially N (Fukuzawa et al, 2006; Watanabe & Fukuzawa, 2013; Shiau et al, 2017; Borisade & Odiwe, 2018). Its rapid growth and abundance (Yang et al, 2014) may contribute to nutrient pumping, whereby nutrients leached deep into the soil are deposited at the surface as bamboo litterfall (Christanty, Kimmins & Mailly, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Bamboo density effects the dynamics and structure of forests (Tabarelli & Mantovani, 2000; Griscom & Ashton, 2003; Giordano, Sánchez & Austin, 2009; Rother, Rodrigues & Pizo, 2009; Lima et al, 2012), serving as a resource for different animals (Reid et al, 2004; Areta, Bodrati & Cockle, 2009; Hilário & Ferrari, 2010; Cestari & Bernardi, 2011). Although it is unclear whether they influence ecosystem function, studies in this regard have increased and demonstrate the role of bamboo in recovering soil fertility (Christanty, Kimmins & Mailly, 1997), especially nitrogen (Singh & Singh, 1999; Embaye et al, 2005; Fukuzawa et al, 2006; Watanabe & Fukuzawa, 2013; Shiau et al, 2017; Borisade & Odiwe, 2018). …”
Section: Introductionmentioning
confidence: 99%